2020
DOI: 10.3389/fpsyg.2020.01919
|View full text |Cite
|
Sign up to set email alerts
|

Understanding When Similarity-Induced Affective Attraction Predicts Willingness to Affiliate: An Attitude Strength Perspective

Abstract: Individuals reliably feel more attracted to those with whom they share similar attitudes. However, this affective liking does not always predict affiliative behavior, such as pursuing a friendship. The present research examined factors that influence the extent to which similarity-based affective attraction increases willingness to affiliate (i.e., behavioral attraction)-one potential step toward engaging in affiliative behavior. Research on attitude strength has identified attitude properties, such as confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…A mechanism of the relational spreading of psychological capital (Story et al, 2013) within the social group is through behaviours that favour in-group members to out-group members and through the recognition, acknowledgement, appreciation and support of in-group members by those in power (see similarity-attraction effect, Montoya & Horton, 2013, Hartmann, 2000. This idea is supported by the finding that people tend to trust others who are similar to them (Williams, 2001), are more likely to affiliate with them (Philipp-Muller et al, 2020), share more information with them (Harrison et al, 2002) and are more likely to mentor them (Dreher & Cox, 1996). Relationships of mutual trust and recognition offer economic benefits, for example annual compensation advantage for in-group members (Dreher & Cox, 1996), or psychological benefits, for example better organisational adjustment of newcomers (Zheng et al, 2020).…”
Section: Within-group Transfer and Maintenance Of Psychological Capitalmentioning
confidence: 99%
“…A mechanism of the relational spreading of psychological capital (Story et al, 2013) within the social group is through behaviours that favour in-group members to out-group members and through the recognition, acknowledgement, appreciation and support of in-group members by those in power (see similarity-attraction effect, Montoya & Horton, 2013, Hartmann, 2000. This idea is supported by the finding that people tend to trust others who are similar to them (Williams, 2001), are more likely to affiliate with them (Philipp-Muller et al, 2020), share more information with them (Harrison et al, 2002) and are more likely to mentor them (Dreher & Cox, 1996). Relationships of mutual trust and recognition offer economic benefits, for example annual compensation advantage for in-group members (Dreher & Cox, 1996), or psychological benefits, for example better organisational adjustment of newcomers (Zheng et al, 2020).…”
Section: Within-group Transfer and Maintenance Of Psychological Capitalmentioning
confidence: 99%
“…When morality is construed in this manner, there is ample and consistent evidence for the effect of it on behavioral outcomes. For starters, work in the psychological and political domains has found that perceiving a moral basis to one's attitude is a property that contributes to an attitude's strength (Petty & Krosnick, 1995; see Luttrell & Sawicki, 2020;Philipp-Muller, Wallace, Sawicki, et al, 2020;Xu & Petty, in press). Strong attitudes are those that are "durable and impactful" .…”
Section: The Attitude-level Approachmentioning
confidence: 99%
“…Strong attitudes are those that are "durable and impactful" . For example, individuals whose attitudes are perceived to have a moral basis, are more likely to vote in political elections for an attitude-consistent candidate (Ryan, 2014), be repulsed by those who disagree with their morally-based position (Philipp-Muller, Wallace, & Wegener, 2020; Skitka et al, 2005), interpersonally advocate on behalf of their attitude (Philipp-Muller, Wallace, Sawicki, et al, 2020), and even tolerate vigilante violence against those who behave in attitude-inconsistent ways (Skitka & Houston, 2001). In this manner, attitudes that are strengthened because they are perceived to be based in morality are quite similar to attitudes that are strengthened for other reasons (e.g., they are held with great confidence; Tormala & Rucker, 2018).…”
Section: The Attitude-level Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Recipients might feel that a source is similar to themselves insofar as that speaker's vocal affect mirrors (versus clashes with) their own emotions. Given that people prefer similar over dissimilar others (Burleson & Denton, 1992;Philipp-Muller et al, 2020), they may also feel more liking for a source whose vocal affect suggests shared emotional experiences to themselves. In turn, liking a message's source may improve communication success (Roskos-Ewoldsen & Fazio, 1992).…”
Section: Extensions To the Civa Modelmentioning
confidence: 99%